Jmjd1c is dispensable for healthy adult hematopoiesis and Jak2V617F-driven myeloproliferative disease initiation in mice. - Hans F Staehle; Johannes Heinemann; Albert Gruender; Anne M Omlor; Heike Luise Pahl; Jonas Samuel Jutzi (PLoS ONE, 2020)
The histone demethylase JMJD1C is overexpressed in patients with myeloproliferative neoplasms (MPNs) and has been implicated in leukemic stem cell function of MLL-AF9 and HOXA9-driven leukemia. In the emerging field of histone demethylase inhibitors, JMJD1C therefore became a potential target. Depletion of Jmjd1c expression significantly reduced cytokine-independent growth in an MPN cell line, indicating a role for JMJD1C in MPN disease maintenance. Here, we investigated a potential role for the demethylase in MPN disease initiation. We introduced a Cre-inducible JAK2V617F mutation into Jmjd1c knockout mice. We show that Jmjd1c is dispensable, both for healthy hematopoiesis as well as for JAK2V617F-driven MPN disease initiation. Jmjd1c knockout mice did not show any significant changes in peripheral blood composition. Likewise, introduction of JAK2V617F into Jmjd1c-/- mice led to a similar MPN phenotype as JAK2V617F in a Jmjd1c wt background. This indicates that there is a difference between the role of JMJD1C in leukemic stem cells and in MPN. In the latter, JMJC domain-containing family members may serve redundant roles, compensating for the loss of individual proteins.